2008
DOI: 10.1002/pat.1175
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, toughness mechanism, and thermal properties of hyperbranched epoxy modified diglycidyl ether of bisphenol A (DGEBA) interpenetrating polymer networks

Abstract: New hyperbranched poly(trimellitic anhydride-triethylene glycol) ester epoxy (HTTE) is synthesized and used to toughen diglycidyl ether of bisphenol A (DGEBA) 4,4(-diaminodiphenylmethane (DDM) resin system. The effects of content and generation number of HTTE on the performance of the cured systems are studied in detail. The impact strength is improved 2--7 times for HTTE/ DGEBA blends compared with that of the unmodified system. Scanning electron microscopy (SEM) of fracture surface shows cavitations at cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 39 publications
4
64
0
Order By: Relevance
“…Several authors reported that the addition of HBPs reduced the T g of the modified thermosets due to the aliphatic nature of the HBPs studied. [1,2,31,32] In the present study, the presence of aromatic structures and the covalent linkage of phenolic groups to the epoxy matrix help the T g of the materials to be practically maintained, but in general a slight decrease is observed on increasing the proportion of modifier. On decreasing the DB of the GBPEX this value also decreases due to the reduction of covalent bonding of the modifier to the epoxy matrix.…”
Section: Study Of the Curing Processmentioning
confidence: 89%
“…Several authors reported that the addition of HBPs reduced the T g of the modified thermosets due to the aliphatic nature of the HBPs studied. [1,2,31,32] In the present study, the presence of aromatic structures and the covalent linkage of phenolic groups to the epoxy matrix help the T g of the materials to be practically maintained, but in general a slight decrease is observed on increasing the proportion of modifier. On decreasing the DB of the GBPEX this value also decreases due to the reduction of covalent bonding of the modifier to the epoxy matrix.…”
Section: Study Of the Curing Processmentioning
confidence: 89%
“…[26][27][28][29] But for poly(urethane-imide) modified epoxy resin, the T max1 of epoxy resin at 202.0 o C disappeared while shift to higher temperature. It suggests that there is no dehydration of hydroxyl occurs due to the reaction of -NCO of the polyurethane and -OH of epoxy resin, which is also consistent with the IR analysis.…”
Section: Resultsmentioning
confidence: 89%
“…[2][3][4][5] The most feasible approach of improving the properties of epoxy resins is incorporating general additive or reactive-type compounds within them. Three approaches have been adopted in previous studies to eliminate the brittleness of epoxy resins while ensuring high impact strengths and elongations after curing: (1) adding or in situ formation of rubber or thermoplastic particles into the epoxy matrix (these materials act merely as additives), [6][7][8] (2) introducing long-chain molecules into the epoxy resins during the curing process, 9,10 and (3) increasing the crosslinking density or enhancing the strength and number of intermolecular forces. 5,[11][12][13] The major problem encountered with the first two methods are incompatibility between the modifiers and epoxy resins which leading to the decrease of glass transition temperatures (T g ) and phase separation.…”
Section: Introductionmentioning
confidence: 99%